2022
DOI: 10.3400/avd.oa.22-00012
|View full text |Cite
|
Sign up to set email alerts
|

Management of Acute Limb Ischaemia Due to COVID-19 Induced Arterial Thrombosis: A Multi-Centre Indian Experience

Abstract: Objective: To determine the outcomes following various surgical and medical treatments of Coronavirus disease 2019 (COVID-19) induced acute limb ischaemia. Methods: A retrospective study of patients presenting with COVID induced arterial ischaemia in three hospitals from Southern India during the months of May 2020 to August 2021 was undertaken. These patients were managed by either thrombectomy, primary bypass, thrombolysis, anticoagulation or primary amputation based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…Clinical and demographic characteristics of the patients with ALI and COVID-19 in our study were similar to those reported by others [ 11 , 12 , 18 ]. The majority of patients were male in a seventh decade of their life and with multiple comorbidities.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Clinical and demographic characteristics of the patients with ALI and COVID-19 in our study were similar to those reported by others [ 11 , 12 , 18 ]. The majority of patients were male in a seventh decade of their life and with multiple comorbidities.…”
Section: Discussionsupporting
confidence: 89%
“…Upper limb ischemia was diagnosed approximately in one quarter of observations. Other authors [ 11 , 17 ] provide similar results with exception of the study published by Sekar et al , where only 29% of cases were categorized as Rutherford IIB [ 18 ]. It is worth to mention that in our study anatomic location of arterial occlusion, severity and duration of ischemia were similar in infected and non-infected patients as well as mean preoperative ABI value.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations